Study on solvation of aluminium, magnesium and sodium ions in water-urea mixtures with use of ultrasonic and densitometric methods - JUSZKIEWICZ, A.; WĘGIEL, W. (Archives of Acoustics, 1994)
The measurements of ultrasonic wave velocity and density of ternary mixtures: electrolyte-urea-water and quaternary mixtures electrolyte-urea-water-ethanol with AlCl3, Al(NO3)3, MgCl2 and NaCl as electrolytes have been carried out in the temperature range of 15 to 35°C. Analysis of the results indicates that urea molecules participate in the solvation structures of the Al3+ ions but not those of Mg2+ and Na+ ions. A model for the structure of the mixed solvation sphere around the Al3+ ion has been suggested.